2013
DOI: 10.1155/2013/806203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soft Tissue Cephalometric Norms between Turkish and European‐American Adults

Abstract: One of the most important components of orthodontic diagnosis and treatment planning is the evaluation of the patient's soft tissue profile. The main purpose of this study was to develop soft-tissue cephalometric standards for Turkish men and women and compare them with the cephalometric standards of normal European-American white people. The sample included 96 Turkish adults (48 women, 48 men), aged 20 to 27 years. Turkish subjects have increased facial convexity associated with retruded mandible, more obtuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
3
18
0
4
Order By: Relevance
“…Similar results were obtained by the researchers of the Turkish population [2], and pointed to the existence of sexual differences. Cephalometric analysis of the Tweed held at the Bangladesh study population showed differences in the angular characteristics of the cranial complex in relation to the proposed standards [16].…”
supporting
confidence: 90%
“…Similar results were obtained by the researchers of the Turkish population [2], and pointed to the existence of sexual differences. Cephalometric analysis of the Tweed held at the Bangladesh study population showed differences in the angular characteristics of the cranial complex in relation to the proposed standards [16].…”
supporting
confidence: 90%
“…En 1980 Legan HL, Burstone CJ. introducen un estudio cefalométrico en donde analizan los tejidos blandos de la cara y determinan una relación armónica entre dichos tercios con el objeto de definir parámetros estéticos aplicables en cirugía ortognática, para ello, analizaron pacientes caucásicos que no manifiesten desarmonías faciales, no hayan tenido tratamientos de ortodoncia previos y tampoco pérdida de piezas dentales, estos pacientes eran considerados armónicos a la inspección clínica, dentro de las múltiples medidas determinadas las relacionadas establecidas entre la distancia Glabela a Sub Nasal y Sub Nasal a Menton Blando guardan una proporción existente de 1:1 en promedio (10) ; en base a estos estudios Celebi et al (11) analizaron otras poblaciones étnicas y replicaron el estudio cefalométrico en la población turca encontrando una relación equivalente de 1,05:1 con una Desviación Estándar (DE) de 0,1; resultados similares fueron observados por Uysal et al en una población de la misma etnia, así mismo, estudios en otras poblaciones como lo efectuados por Issacson en China, Alcalde en Japón, Jain en India del Norte, Albarakati en Arabia Saudita y Gunaid en la población Yemen (11) , establecen relaciones similares y que pueden ser observados en la tabla 1, si bien no corresponden exactamente a la determinada en los pacientes caucásicos las discrepancias serían mínimas pero no se ha podido determinar si la variación es estadísticamente significativa (11) .…”
Section: Resultados Y Discusión ¿Cuál Es La Dimensión Vertical Oclusaunclassified
“…La relación proporcional entre los segmentos medio e inferior de la cara no son estándar y varían de acuerdo a los diferentes estudios ya sean a través de medidas clínicas (6,12,13,14,15) o estudios cefalométricos (12) , la edad de los pacientes, el sexo, la etnia, e incluso el número de la población estudiada influyen para que los datos obtenidos no sean estandarizados a cada individuo, sin embargo se puede inferir de acuerdo a los hallazgos encontrados en la literatura que la relación obtenida entre los puntos Subnasal y Glabela (11) , así como, la distancia entre los puntos medidos desde el canto externo del ojo hasta la comisura de la boca (Método de Willis) (12) en el tercio medio de la cara, pueden ser utilizados como puntos de referencia para determinar la DVO, puesto que guardan una estrecha relación con el punto Subnasal mentón blando del tercio inferior del rostro (11) . Un resumen esquemático de la relación más proximal entre los diferentes estudios es representado en la Figura 1.…”
Section: Resultados Y Discusión ¿Cuál Es La Dimensión Vertical Oclusaunclassified
See 1 more Smart Citation
“…Some studies have evaluated skeletal and softtissue cephalometric norms for Anatolian Turkish people. [35][36][37][38][39] According to Basciftci et al, 35 most of the values for skeletal measurements in Anatolian Turkish adults were found to be similar to the ideal norms of Steiner. 35 Uysal et al 38 found that the Turkish sample had a more retrognathic maxilla and mandible and a more vertical direction of facial development when compared with Saudi young adults.…”
Section: Discussionmentioning
confidence: 99%